Gagne's Nine Events in Mobile-Assisted Vocabulary Learning for Higher Education - Nasrullah, Muhammad; Ulfa, Saida; Rochmahwati, Pryla (Al-Hayat: Journal of Islamic Education, 2024)
This study aims to develop a mobile application based on Nine Events Gagne to improve vocabulary mastery of Arabic research methodology. The application was developed using the ADDIE Model, involving four lecturers as expert evaluators and 25 6th-semester students as end users. Data were collected through a combined method: qualitative feedback from content and instructional design experts and quantitative data from lecturer and expert questionnaires. The application trial was conducted during eight meetings at State Islamic Institute (IAIN) Ponorogo to evaluate the practicality and effectiveness of the application in improving vocabulary mastery. The development of Nine Instructional Design Events Gagne in Mobile-Assisted Vocabulary Learning began with analysing student needs, learning styles, and learning objectives to design an application to support research vocabulary learning. The design stage includes pre-class analysis, knowledge context, review process, and design of learning activities. The results of the material expert test showed that 92% of the vocabulary was by academic topics, with an average score of 4.5/5. The media test showed that the application design was very positive, with a score of 4.6/5 for ease of use and interactivity and 4.7/5 for visual design. As many as 90% of respondents considered the interactive features effective in improving vocabulary comprehension. The effectiveness test using a paired sample t-test on 25 students showed a significant increase in pre-test and post-test scores, with a t-value of 10.627 and a p-value <0.001. This mobile application successfully improved student comprehension, retention, and engagement through semantic mapping, gamification, and immediate feedback. The study's limitations were the limited number of samples and the focus only on vocabulary. Further research is recommended to expand the scope of the application and sample to explore long-term impacts.